Reinterpretasi Filosofis Mitos Seputar Kehamilan dalam Masyarakat Jawa di Surakarta: Dari Imajinatif Kreatif Menuju Filosofis yang Dinamis - Waryunah Irmawati (UIN Raden Mas Said Surakarta, 2018)
The issue is a matter of trust myths contained in the community, which can be thought although not an outcome logic, but not forever the myth of no benefit in people's lives. Myth in view of the philosophical meaning that is both ethics and eistetics. With the understanding of the philosophical community is expected not easily blame others, by giving criticism that it does not need to believe in the myth because it would be detrimental to humans. The approach taken in this research is descriptive qualitative field research. The results of this study indicate that the myths surrounding pregnancy are believed by the public basically has values that can be used in public life who believe in it. Ethics, there is value obedience,Â kindness to health, caution, alert,Â polite and hard-working teachings. While the aesthetic dimension is a subjective aesthetic, in whichÂ balancing theory with characteristic feature has a value of unity, the value of complexity, and the value of seriousness, which is visible in color, words and shapes